Map of Newfoundland - The South Publishing Co. (Publisher)
Map of Newfoundland published in 1899. Highlights lighthouses, railway and steamship routes (see legend in the top right-hand corner). Mountains (with elevation spot heights) and other topographic features drawn with hashed lines. Names of towns and bodies of water are seen throughout. Scale is 1 : 850,000. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .